A dentin-derived hydrogel bioink for 3D bioprinting of cell laden scaffolds for regenerative dentistry. (10th January 2018) - Athirasala, Avathamsa; Tahayeri, Anthony; Thrivikraman, Greeshma; França, Cristiane M; Monteiro, Nelson; Tran, Victor; Ferracane, Jack; Bertassoni, Luiz E
Abstract: Recent studies in tissue engineering have adopted extracellular matrix (ECM) derived scaffolds as natural and cytocompatible microenvironments for tissue regeneration. The dentin matrix, specifically, has been shown to be associated with a host of soluble and insoluble signaling molecules that can promote odontogenesis. Here, we have developed a novel bioink, blending printable alginate (3% w/v) hydrogels with the soluble and insoluble fractions of the dentin matrix. We have optimized the printing parameters and the concentrations of the individual components of the bioink for print accuracy, cell viability and odontogenic potential. We find that, while viscosity, and hence printability of the bioinks, was greater in the formulations containing higher concentrations of alginate, a higher proportion of insoluble dentin matrix proteins significantly improved cell viability; where a 1:1 ratio of alginate and dentin (1:1 Alg-Dent) was most suitable. We further demonstrate high retention of the soluble dentin molecules within the 1:1 Alg-Dent hydrogel blends, evidencing renewed interactions between these molecules and the dentin matrix post crosslinking. Moreover, at concentrations of 100 μ g ml −1, these soluble dentin molecules significantly enhanced odontogenic differentiation of stem cells from the apical papilla encapsulated in bioprinted hydrogels. In summary, the proposed novel bioinks have demonstrable cytocompatibility and natural odontogenic capacity, which can be a used to reproducibly fabricate scaffolds with complex three-dimensional microarchitectures for regenerative dentistry in the future.